Grid, Group, and Grade: Challenges in Operationalizing Cultural Theory for Cross-National Research. (July 2015) - Maleki, Ammar; Hendriks, Frank
Grid–Group Cultural Theory (CT), developed by Mary Douglas and followers, is a well-known and often-used framework for the analysis of culture in the political–administrative world. Although Douglas herself was rather wary of detailed operationalization of CT, many scholars have tried to measure Grid and Group and tested implications of the theory along these dimensions at different levels of analysis, within or between nations. In this article, we recognize and discuss some grave challenges surrounding the operationalization of Grid and Group, particularly at the cross-national level. Presenting distinct facets of Group and Grid, we debate that in some measurements, divergent and unrelated cultural attributes are used in the operationalization of Grid and Group, making validity and reliability of such operationalization problematic. We also exhibit that Grid and Group cannot cover some cultural variances between or within societies; hence, we introduce and elaborate on a third dimension: "Grade." We demonstrate that this dimension is missing and much-needed in CT.